2020
DOI: 10.1101/2020.01.08.899609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapy-induced lipid uptake and remodeling underpin ferroptosis hypersensitivity in prostate cancer

Abstract: 29Background 30 Metabolic reprograming, non-mutational epigenetic changes, increased cell plasticity and 31 multidrug tolerance are early hallmarks of therapy resistance in cancer. In this temporary, 32 therapy-tolerant state, cancer cells are highly sensitive to ferroptosis, a form of regulated cell 33 death that is caused by oxidative stress through excess levels of iron-dependent peroxidation 34 of polyunsaturated fatty acids (PUFA). However, mechanisms underpinning therapy-induced 35 ferroptosis hype… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…In the context of prostate cancer, it has been shown that DECR1 is an androgen-regulated survival protein that protects cells from ferroptosis and targeting DECR1 induces ferroptosis (42). In addition, treatment with enzalutamide induces lipid peroxidation and leads to sensitivity to GPX4 inhibition and ferroptosis in vitro (43). However, the therapeutic potential of ferroptosis inducers erastin and RSL3 in prostate cancer has not been tested in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of prostate cancer, it has been shown that DECR1 is an androgen-regulated survival protein that protects cells from ferroptosis and targeting DECR1 induces ferroptosis (42). In addition, treatment with enzalutamide induces lipid peroxidation and leads to sensitivity to GPX4 inhibition and ferroptosis in vitro (43). However, the therapeutic potential of ferroptosis inducers erastin and RSL3 in prostate cancer has not been tested in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, targeting DECR1 causes cellular accumulation of PUFAs, enhanced mitochondrial oxidative stress and lipid peroxidation, and induced ferroptosis 67 . In another study, enzalutamide was found to induce extensive phospholipid remodeling and increase membrane PUFA levels, causing hypersensitivity to ferroptosis 68 . These studies provide insight into development of novel therapeutics for advanced prostate cancer that target lipid metabolism and the ferroptosis pathway.…”
Section: Emerging Signaling Pathways In Mcrpcmentioning
confidence: 90%
“…As mentioned previously, PUFA ≥4 is broadly representative of "dietary" FAs, and its increase amongst all monitored dn-GPLs after PA or SA supplementation suggests that these PUFAs are being sourced and remodelled from another lipid class, such as other GPLs or more likely, being sequestered from triacylglycerols (TG). [27][28] Interestingly, within the dn-13SA profiles an increase within the PC 40:5, PC 40:6 and PE, PS, PI 40:6 could be observed. This is in contrast to the up-13SA profiles, where PS, and PE, 40:5 and 40:6 were seen to decrease.…”
Section: Influence Of Saturated Fa Supplements On Unsaturated Membrane Lipidsmentioning
confidence: 92%